Formal Methods for Industrial Critical Systems: 26th International Conference, FMICS 2021, Paris, France, August 24-26, 2021, Proceedings - International Conference on Formal Methods for Industrial Critical Systems; Lafuente, Alberto Lluch; Mavridou, Anastasia (Lecture Notes in Computer Science, 2021)
This book constitutes the proceedings of the 26th International Workshop on Formal Methods for Industrial Critical Systems, FMICS 2021, which was held during August 24-26, 2021. The conference was planned to take place in Pairs, France. Due to the COVID-19 pandemic it changed to a virtual event.The 10 full papers and 6 short papers presented in this volume were carefully reviewed and selected from 31 submissions. The papers are organized in topical sections as follows: Verification, Program Safety and Education, (Event-)B Modeling and Validation, Formal Analysis, Tools, Test Generation and Probabilistic Verification.